The "String of Pearls" technique for increased surface area and lymphedematous fluid drainage in right gastroepiploic‐vascularized lymph node transfer: A report of two cases. Issue 6 (21st June 2019) - Fan, Kenneth L.; Black, Cara K.; Song, David H.; Del Corral, Gabriel A.
Abstract: We present our "String of Pearls" technique for upper and lower extremity lymphedema based off the right gastroepiploic artery. The entire laprascopically harvested omentum is placed through a longitudinal incision at the lymphedematous area, and anastomosed proximally, with additional distal venous outflow. This approach preserves the native lymphaticovenous architecture, distributes free lymphatic tissue along the axis of the extremity, and allows for scar release. The additional vein serves to restore bidirectional physiologic drainage inherent in the omentum and providing further lymphaticovenous drainage. We present two cases of upper and lower extremity lymphedema as a result of malignancy treated using this method. The first case was a result of breast cancer in a 55‐year‐old female with orthotopically placed omentum, and the second case a result of malignant nodular fasciitis in the distal lower extremity in a 56‐year‐old female with distally placed omentum. No complications occurred. At 3 months follow up, there is a 25% and 28% reduction in lower and upper extremity volume, respectively, with no recurrent cellulitis episodes. The safety and feasibility of placement of the entire omentum longitudinally with additional venous anastomosis are apparent. However, long‐term studies are required.